Chromatography : Concepts and Contrasts - Miller, James M. (John Wiley & Sons, 2009)
The first edition of Chromatography: Concepts and Contrasts, published in 1988, was one of the first books to discuss all the different types of chromatography under one cover. The second edition continues with these principles but has been updated to include new chapters on sampling and sample preparation, capillary electrophoresis and capillary electrochromatography (CEC), chromatography with mass spec detection, and industrial and governmental practices in regulated industries. Covers extraction, solid phase extraction (SPE), and solid phase microextraction (SPME), and introduces mass spectrometry Updated with the latest techniques in chromatography Discusses both liquid chromatography (LC)and gas chromatography(GC)